Vulnerability of women to Aids: a study of mortality according to years of potential life lost (ypll) - Carneiro da Silva Prata, Maiky; Yasuko Izumi Nichiata, Lúcia; Ferreira Takahashi, Renata; Bertolozzi, Maria Rita (O Mundo da Saúde, 2009)
This is an epidemiologic, descriptive and temporal study. It describes female mortality by AIDS in the 17 Regional Health Departments (DRS) of São Paulo State, by means of years of potential life lost (YPLL) and identifies relations between occurrence of early death by AIDS and life conditions. Data was obtained in the database of Sistema de Informação de Agravos de Notificação (SINAN), which records deaths. 16973 women were studied, with ages from 15 to 69 years that died from 01/01/1985 the 12/31/2006. YPLL was calculated and its rates (TAPVP) for the 17 DRS. We used as social indexes the São Paulo Index of Social Responsibility (IPRS), the São Paulo Index of Social Vulnerability (IPVS) and rates regarding Completed Study Years (AEC). There was a reduction of deaths by AIDS from 1996 on, predominance of school years low rates and increase of survival. We did not observe a direct relationship between IPRS, TAPVP and IPVS. Considering social indexes bases as determinative of early mortality, it was evidences the necessity of enhancing AIDS control strategies among São Paulo women.